Effectiveness of Digital Interventions Based on Mobile Phones for the Prevention of Sexually Transmitted Infections: A Systematic Review Protocol [Efectividad de Las Intervenciones Digitales Basadas en Teléfonos Móviles Para la Prevención de Infecciones de Transmisión Sexual: Protocolo de Revisión Sistemática] - Duarte-Anselmi, G; Vanegas-Lopez, J (Medwave Estudios Ltda, 2019)
Introduction Sexually transmitted infections, including HIV, are an important public health problem. Every day, over one million persons become infected with a sexually transmitted infection (STI). Health systems are searching for solutions to improve sex education and change the sexual behavior of people in order to prevent them. In public health, digital interventions based on mobile health technologies (M-health), especially those based on mobile phones, might be a crucial tool for the prevention of STIs and HIV. This systematic will review and summarize the evidence on the effectiveness of mobile phone-based interventions for the prevention of STIs and HIV. Methods and analysis The protocol was designed and will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P). The protocol will include randomized controlled trials that assess the effect of interventions based on mobile phones for the prevention of STIs/HIV. The interventions of interest will be those targeting mobile phone users and should consist of providing information by mobile phone through any function or application that can be used or sent to, and that has been designed to educate, promote or modify sexual behaviors and prevent STIs, including HIV. The data sources to identify these studies will be the Cochrane Central Register of Controlled Trials (CENTRAL), EMBASE and MEDLINE. The risk of bias will be assessed using the tool recommended by Cochrane. Finally, a meta-analysis will be done and data will be presented following the GRADE method. Ethics and dissemination This research was exempted by the Ethics Committee of Pontificia Universidad Católica de Chile (ID 171128002). © 2019, Medwave Estudios Ltda. All rights reserved.